The isolation of sub-saharan floating currencies - Kiss Gábor Dávid (ACTA ACADEMICA KARVINIENSIA, 2015)
The paper tested contagion effects among free floating African currencies and Euro with a control variable like the Euro-pegged CFA Franc. Contagion should be based on deep trade, funding and political relationships which was valid for connections between African countries and such developed countries like the United States or the Eurozone. The theory suggests increased common movements under shock periods which were tested on a daily time series between 2000 and 2015, studying relationships under recession periods in the United States or the Eurozone or under days with extreme fluctuation. The results presented contagions only for the emerging South African currency while the others proved to be relatively independent.